Where do all the lost things go? - Hafizah Abdul Wahid (2010)
If you were to ask me what first drew me to animation, I would say this – storytelling. At heart, I am a crafter of stories and a weaver of tales. For me, the story is the most crucial building block of any type of film. Without a solid story, a film can still be good, but it can never be extraordinary. But in a film, the story cannot exist by itself. Other elements such as the art direction, animation and music are just as crucial, and will complement if not strengthen the storytelling. While “Where Do All The Lost Things Go?” was a singular idea born out of my own imagination, it was the collaborative efforts of the four minds that make up Hakajober (our group name comprising of the first syllable of our first names) that gave my story its breath of life. As the storyteller, I aimed to create a unique and outstanding narrative. But as the director, it was also demanded of me to tell that story through a film whose elements integrated cohesively with the narrative and vice versa. Much of my efforts put into this film were to find that balance, and it is only with the brilliant contributions of my teammates that I was able to achieve this goal. “Where Do All The Lost Things Go?” is their story as much as it is mine.